Academic Advocacy: Opportunities to Influence Health and Science Policy Under U.S. Lobbying Law. (January 2020) - Fernandez Lynch, Holly; Bateman-House, Alison; Rivera, Suzanne M.
Abstract : Medical school faculty and their colleagues in schools of nursing, public health, social work, and elsewhere often research issues of critical importance to health and science policy. When academics engage with government policymakers to advocate for change based on their research, however, they may find themselves engaged in "lobbying, " thereby entering a complex environment of legal requirements and institutional policies that they may not fully understand. To promote academic advocacy, this article explains what is and is not legally permitted when it comes to engaging with policymakers and encourages academic institutions to facilitate permissible advocacy activities. U.S. law permits academic researchers to conduct certain types of policy-focused advocacy without running afoul of legal restrictions on lobbying. Academics acting in their personal capacities and with their own resources may freely engage with policymakers in any branch of government to provide their expertise and advocate for desired outcomes. When acting in their professional capacities, academics are free to engage in most advocacy activities directed to the executive and judicial branches, and they also may advocate to influence legislation and legislators within certain limits that are particularly relevant to academic work. In all cases, academics must take care to not use restricted funds for lobbying. Academic researchers have an important role to play in advancing evidence-based health and science policy. They should familiarize themselves with legal restrictions and opportunities to influence policy based on their research, and their institutions should actively support them in doing so.